Modeling Diauxic Glycolytic Oscillations in Yeast - Hald, Bjørn Olav (The Biophysical Society, 2010)
Glycolytic oscillations in a stirred suspension of starved yeast cells is an excellent model system for studying the dynamics of metabolic switching in living systems. In an open-flow system the oscillations can be maintained indefinitely at a constant operating point where they can be characterized quantitatively by experimental quenching and bifurcation analysis. In this article, we use these methods to show that the dynamics of oscillations in a closed system is a simple transient version of the open-system dynamics. Thus, easy-setup closed-system experiments are also useful for investigations of central metabolism dynamics of yeast cells. We have previously proposed a model for the open system comprised of the primary fermentative reactions in yeast that quantitatively describes the oscillatory dynamics. However, this model fails to describe the transient behavior of metabolic switching in a closed-system experiment by feeding the yeast suspension with a glucose pulse—notably the initial NADH spike and final NADH rise. Another object of this study is to gain insight into the secondary low-flux metabolic pathways by feeding starved yeast cells with various metabolites. Experimental and computational results strongly suggest that regulation of acetaldehyde explains the observed behavior. We have extended the original model with regulation of pyruvate decarboxylase, a reversible alcohol dehydrogenase, and drainage of pyruvate. Using the method of time rescaling in the extended model, the description of the transient closed-system experiments is significantly improved.